A91: The Development and Initial Evaluation of a Standardised Play Based Hand Assessment Tool for Use in Children and Adolescents: the PizzaPutty™ Test. Issue 11 (March 2014) - Leese, Stephanie; Hackett, Janine; Aslam, Riffat; Mills, Lisa; Jester, Andrea; Southwood, Taunton R.
Abstract : Background/Purpose: A wide variety of diseases affect the hands in children and adolescents, ranging from relatively static congenital structural abnormalities to progressively destructive inflammatory conditions including juvenile idiopathic arthritis (JIA). Measuring the natural history of such conditions, and the clinical utility of the surgical or pharmacological treatment, requires standardised, age appropriate hand function assessment tools, but there are relatively few of these available. The aim of our research programme was to develop and evaluate a new standardised hand function assessment tool, the PizzaPutty™ test, in a cohort of subjects with a wide range of hand conditions including congenital hand deformities, inherited metabolic diseases and juvenile idiopathic arthritis with evidence of upper limb involvement. Here we present the initial development details and preliminary evaluation of test feasibility and acceptability in a cohort of children and adolescents with juvenile idiopathic arthritis. Methods: As part of a research collaborative programme led by plastic surgery and occupational therapy, an assessment tool was developed, the PizzaPutty™ test, that objectively evaluates hand dexterity in children and adolescents. It is a play based, standardised grip function test that can be used for children of all ages. It comprises easily obtainable theraputty, a variety of bead sizes, and a set of instructions to guide patients through a series of activities leading to the creation of a simulated pizza. An occupational therapist administers the test, provides patient and family support, and obtains a detailed evaluation of 7 different grip functions and a derived score from grip function score. In some cases, videos were taken for inter‐observer reliability analysis. Results: 34 patients with Juvenile Idiopathic Arthritis (JIA), ranging in age from 2–17 years, (25 girls and 9 boys) were recruited after informed consent from routine rheumatology outpatient clinics at a tertiary referral children's hospital. All patients must have had features of upper limb involvement. JIA subtype distribution: 10 extended oligoarthritis (2 had chronic anterior uveitis without any abnormality of visual acuity), 9 polyarthritis (RF negative), 4 JIA polyarthritis (RF positive), 6 systemic onset, 1 psoriatic arthritis, 3 oligoarthritis, 1 undifferentiated. All patients were able to complete the PizzaPutty™ test in 20 minutes or less (mean 15 minutes, range 10–20 minutes), with the children over 10 years of age accomplishing the test in the fastest times. All participants found it enjoyable, although patients older than 15 years felt that it was "childish" and patients under 3 had some difficulty in maintaining their concentration without encouragment. Unsolicited feedback from the subjects and/or parents was that the test was stimulating and fun. Conclusion: The PizzaPutty™ test appears to be feasible and acceptable for monitoring hand disease in a clinical outpatient setting.